2016
DOI: 10.1016/j.ijpharm.2016.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Drug loaded and ethylcellulose coated mesoporous silica for controlled drug release prepared using a pilot scale fluid bed system

Abstract: The goal of this study was to test the feasibility to load non-ordered, non-spherical mesoporous silica with the model drug paracetamol, and subsequently coat the loaded particles using one single pilot scale fluid bed system equipped with a Wurster insert. Mesoporous silica particles (Davisil(®)) with a size ranging from 310 to 500μm and an average pore diameter of 15nm were loaded with paracetamol to 18.8% drug content. Subsequently, loaded cores were coated with ethylcellulose to obtain controlled drug rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…However, because of high cytotoxicity and non-specificity to tumors, many chemotherapy drugs bring severe side effects, which exert pronounced suffering to patients and make them unfit for long-term therapy 3 - 5 . Currently, among the various approaches to improve the effectiveness of chemotherapy drugs, controlled drug delivery systems that can convey chemotherapeutic drugs safely and efficaciously have attracted great attention 6 - 12 . A desirable controlled release system should: 1) be easy to prepare with high purity; 2) accumulate more in cancer than normal cells; 3) exhibit minimal cytotoxicity to normal cells; 4) have favorable controlled release to prolong the acting time and avoid multiple dosing; 5) enable direct and real-time monitoring of the drug release dynamics with high accuracy in a noninvasive manner 13 - 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, because of high cytotoxicity and non-specificity to tumors, many chemotherapy drugs bring severe side effects, which exert pronounced suffering to patients and make them unfit for long-term therapy 3 - 5 . Currently, among the various approaches to improve the effectiveness of chemotherapy drugs, controlled drug delivery systems that can convey chemotherapeutic drugs safely and efficaciously have attracted great attention 6 - 12 . A desirable controlled release system should: 1) be easy to prepare with high purity; 2) accumulate more in cancer than normal cells; 3) exhibit minimal cytotoxicity to normal cells; 4) have favorable controlled release to prolong the acting time and avoid multiple dosing; 5) enable direct and real-time monitoring of the drug release dynamics with high accuracy in a noninvasive manner 13 - 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The material temperature played an important role in the coating quality and the in vitro release profile of the products (Hacene, Singh, & Van den Mooter, ). Different material temperatures (26, 28, 30. and 32°C) were tested, and the results of the in vitro release behavior at pH 1.2 revealed that the release rate of DMOP at 26°C was significantly higher than that at other temperatures (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The material temperature played an important role in the coating quality and the in vitro release profile of the products (Hacene, Singh, & Van den Mooter, 2016). Different material temperatures (26,28,30.…”
Section: Preparation and Optimization Of Dmopmentioning
confidence: 99%
“…First, the poor biodegradability of MSNs leads to toxic bioaccumulation after long‐term administration. Second, when the drug‐loaded MSNs are internalized into cancer cells, only a portion of the drug releases from the nanoparticles; much of the drug remains in the pore canal and cannot exert its anticancer effect . This incomplete release limits the therapeutic effect of the drug‐loaded MSNs.…”
Section: Introductionmentioning
confidence: 99%